РОЗРАХУНОК ІНВЕРТУЮЧОГО ПЕРЕТВОРЮВАЧА ПОСТІЙНОЇ НАПРУГИ З УРАХУВАННЯМ РЕЖИМІВ РОБОТИ МЕТОДОМ УСЕРЕДНЕННЯ - Ю.В. Руденко; Д.В. Мартинов (Праці Інституту електродинаміки Національної академії наук України)
Electromagnetic processes in the buck-boost dc converter are investigated with respect to operating modes using the averaging method based on Lagrange theorems. In the continuous conduction mode (CCM), two internal submodes are considered: incomplete inductor supply mode (IISM) and complete inductor supply mode (CISM) depending on the ratio of the load direct current and minimum inductor current value. Analytical expressions are obtained for calculating the average and ripple values of currents and voltages in the reactive elements of converter, as well as their ripple coefficients for each of the operating modes and submodes. The limiting values of the converter parameters between CISM and IISM submodes in the commutation range are calculated and established. Taking into account the specified submodes allows for more precise calculation of the parameters of buck-boost dc converter. The results of simulation modeling of processes in converter confirmed the validity of the developed analytical relations. Ref. 20, fig. 5, table 2.